The contribution of physical education and sports curricula to improving the basic motor skills of primary school students (8/10 years old) - Merzougui, Samir; layadi, Abdel Hakim; Bourenane , khalil (sports creativity, 2025)
Introduction: The transformations witnessed by the educational system in Algeria, and the challenges it presented, necessitated the development of new approaches to teaching that transcend previous practices. These previous approaches were no longer sufficient to meet the aspirations and challenges imposed upon it. Physical education, like other subjects, has kept pace with these changes, given its crucial role in the lives of individuals and society. It is vital for the holistic development of the individual in all aspects. Proper preparation of the child helps them face the civilizational challenges inherent in the inevitability of progress. Therefore, interest in sports has recently increased to the point where the advancement of sports in any country is now considered a measure of the progress of nations and civilizations (Ahmed, 1998, p. 8). Consequently, it was natural to focus on the sports sciences related to athletic performance. It has been scientifically proven that most sports activities are linked to physical development, and that various forms of play provide individuals with opportunities for organized mental and physical growth. This helps them develop communication and cooperation skills, fosters self-respect and self-esteem, increases their ability to understand the needs of others, and helps them acquire social habits that enable them to adapt to their environment and interact harmoniously with all those they encounter. People (Ibrahim, 2002, page 07), it also works to achieve the hopes and aspirations of peoples. It is not just random movements, but rather a complete education through practice and activity, the first means of which is body movement. Therefore, basic motor skills have a role in practicing all sports activities, as they help the child develop his spatial and temporal world and develop his ability to think correctly, analyze and study.